Peningkatan Pemahaman Siswa SMAN 3 Kota Kediri tentang Pentingnya Hidup Sehat Tanpa Narkoba - Vivien Dwi Purnamasari; Gerardin Ranind Kirana; Reny Nugraheni (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2024)
Education about the dangers of drugs is very important to convey to society, especially to the younger generation. The aim of this community service activity is to increase the knowledge of SMAN 3 Kediri students about the importance of living a healthy life without drugs. The method used is direct lecture and discussion methods. The pre-test and post-test were carried out in the form of 9 statements, then participants were asked to answer whether each statement was true or false. The statements in the pre-test and post-test are adjusted to the material presented, namely the dangers of drugs and types of drugs. The results of this activity were an increase in students' knowledge about drugs, namely that out of a total of 300 students, the average number of correct answers was 60.1% in the pre-test, and increased to 82.07% in the post-test. Community service activities use methods and materials adapted to the younger generation so that they can effectively increase students' knowledge about the importance of living a healthy life without drugs. At the end of the discussion session, ensure the understanding of all participants and invite students to ask questions if there is anything that is not clear. Apart from that, it can end with an important message about the importance of protecting oneself from the dangers of drugs, as well as encouraging people to seek help if students or those in their environment experience drug problems.